Perbandingan Teknik Aerasi dan Ultrasonikasi Gelasi Ionik Nanopartikel Deksametason Natrium Fosfat - Nugroho, Bambang Hernawan; Wardhani, Multi Tri; Suparmi, Suparmi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
Alginate, a biocompatible and biodegradable natural polymer, has been widely used as a drug molecular carrier using ionic gelation methods (crosslinking). One of the factors that must be taken into account in its preparation is the mechanical effect. The purpose of this study was to explain the preparation process and the characteristics of the calcium alginate crosslinkers as dexamethasone sodium phosphate carriers with low energy and high energy techniques. Nanosuspension is made in six formulas using 3 techniques: low energy (aeration), high energy (ultrasonication), low and high energy (aeration and ultrasonication) with a fixed concentration of dexamethasone sodium phosphate and sodium alginate, that is 0,2% and 0,1%, with 0,02% and 0,2% of calcium chloride. Determination of particle size, zeta potential, and morphology of nanoparticles using Particle Size Analyzer (PSA) and Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM). Determination of encapsulation efficiency using UV/Vis spectrophotometer and statistical analysis using MANOVA test. Synthesis of nanosuspension using a combination of low and high energy (aeration and ultrasonication) results in the most optimal characteristics with particle size value of 352.90 ± 6.10 nm, homogenized polydispersity index (0,52 ± 0,04), optimal potential zeta -44,40 ± 0,4 mV, the encapsulation efficiency of 49,5 - 74,8% and spherical particle shape. It can be concluded that the preparation using a combination of low and high energy is the most optimal preparation result.